Penetapan Usia Minimal dalam Rekrutmen Tenaga Kerja Ditinjau dari Prinsip Kesetaraan dan Larangan Diskriminasi dalam Hukum Ketenagakerjaan Indonesia - Kholilul Rohman Afifudin; Dipo Wahyoeono (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The establishment of a minimum age requirement in employee recruitment is a common practice in Indonesia’s labor market and is often justified as part of human resource management and the protection of young workers. However, from the perspective of labor law, such a requirement cannot be separated from the principles of equality and non-discrimination in access to employment. This article aims to conduct a normative analysis of whether the imposition of a minimum age requirement in recruitment, as regulated under Indonesian labor law, contradicts the principle of equality and the prohibition of discrimination. This study employs a normative legal research method using statutory and conceptual approaches. The findings indicate that the regulation of working age under Law Number 13 of 2003 on Manpower contains normative inconsistencies and legal ambiguities, which create opportunities for age-based discrimination in recruitment practices. The rigid and general application of minimum age requirements, without objective justification directly related to the nature of the job, has the potential to violate the principle of equality and the prohibition of discrimination in Indonesian labor law.